What Do Artists Know? - Arya, Rina; Avgita, Louisa; Baetens, Jan; Baker, Su; Boomgaard, Jeroen; Buckley, Brad; Conger, William; Conomos, John; Dahlgren, Anders; Elkins, James; Elkins, James; Fendrich, Laurie; et al. (The Stone Art Theory Institutes, 2021)
Each of the five volumes in the Stone Art Theory Institutes series, and the seminars on which they are based, brings together a range of scholars who are not always directly familiar with one another's work. The outcome of each of these convergences is an extensive and "unpredictable conversation" on knotty and provocative issues about art. This third volume in the series, What Do Artists Know?, is about the education of artists. The MFA degree is notoriously poorly conceptualized, and now it is giving way to the PhD in art practice. Meanwhile, conversations on freshman courses in studio art continue to be bogged down by conflicting agendas. This book is about the theories that underwrite art education at all levels, the pertinent history of art education, and the most promising current conceptualizations. The contributors are Areti Adamopoulou, Glenn Adamson, Rina Arya, Louisa Avgita, Jan Baetens, Su Baker, Ciarín Benson, Andrew Blackley, Jeroen Boomgaard, Brad Buckley, William Conger, John Conomos, Christopher Csikszentmihályi, Anders Dahlgren, Jonathan Dronsfield, Marta Edling, Laurie Fendrich, Michael Fotiadis, Christopher Frayling, Miguel González Virgen, R.E.H. Gordon, Charles Green, Vanalyne Green, Barbara Jaffee, Tom McGuirk, William Marotti, Robert Nelson, Håkan Nilsson, Saul Ostrow, Daniel Palmer, Peter Plagens, Stephan Schmidt-Wulffen, Howard Singerman, Henk Slager, George Smith, Martin Søberg, Ann Sobiech Munson, Roy Sorensen, Bert Taken, Hilde Van Gelder, Frank Vigneron, Janneke Wesseling, Frances Whitehead, Gary Willis, and Yeung Yang